Representation of Feminism In the Barbie Movie 2023 - Ratri Adinda Oktavdianti (Jurnal Dakwah dan Komunikasi, 2024)
This research aims to understand and analyze the representation of characters in the 2023 Barbie movie, demonstrating signs of feminism. The research employs a qualitative descriptive method. Through semiotic analysis, the representation of female characters in the 2023 Barbie movie, showing signs of feminism, can be understood more deeply. This approach allows researchers to interpret various objects and their relationships as communication symbols. The abstract serves as a summary of the entire article. The research findings indicate that in several scenes in the Barbie movie, there are conflicts and feminist movements within Barbie's character, advocating for her desire to reclaim Barbieland, which has been seized by Ken and transformed into Kendomland. There are several messages conveyed in the Barbie movie, particularly concerning gender equality between men and women in society. Over time, women are no longer confined to household chores but can pursue their desires and dreams. The feminist movement must be carried out in societal life to eliminate the gap between men and women.